Automated Time-Lapse Imaging and Manipulation of Cell Divisions in Arabidopsis Roots by Vertical-Stage Confocal Microscopy - Hoermayer, Lukas; Friml, Jiří; Glanc, Matouš (Methods in molecular biology, 2022)
The analysis of dynamic cellular processes such as plant cytokinesis stands and falls with live-cell time-lapse confocal imaging. Conventional approaches to time-lapse imaging of cell division in Arabidopsis root tips are tedious and have low throughput. Here, we describe a protocol for long-term time-lapse simultaneous imaging of multiple root tips on a vertical-stage confocal microscope with automated root tracking. We also provide modifications of the basic protocol to implement this imaging method in the analysis of genetic, pharmacological or laser ablation wounding-mediated experimental manipulations. Our method dramatically improves the efficiency of cell division time-lapse imaging by increasing the throughput, while reducing the person-hour requirements of such experiments.
Keywords: Arabidopsis; meristém; časosběrné zobrazování; Meristem; Time-Lapse Imaging; lidé; Cell Division; Humans; Microscopy, Confocal; buněčné dělení; konfokální mikroskopie